2018
DOI: 10.1093/molbev/msy213
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Mutational Process under Relaxed Selection inCaenorhabditis elegans

Abstract: The mutational process varies at many levels, from within genomes to among taxa. Many mechanisms have been linked to variation in mutation, but understanding of the evolution of the mutational process is rudimentary. Physiological condition is often implicated as a source of variation in microbial mutation rate and may contribute to mutation rate variation in multicellular organisms. Deleterious mutations are an ubiquitous source of variation in condition. We test the hypothesis that the mutational process dep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(78 citation statements)
references
References 54 publications
12
66
0
Order By: Relevance
“…Our empirical estimate of the spontaneous nuclear base substitution rate for C. elegans is similar to three previous estimates for the species using high-throughput sequencing of MA lines (Denver et al 2009(Denver et al , 2012Saxena et al 2019), but substantially lower than the first estimate, which was based on Sanger sequencing (9.1 3 10 29 ; Denver et al 2004). Additionally, our spontaneous base substitution rate is similar to estimates for the congeneric species C. briggsae (average 1.33 3 10 29 ; Denver et al 2012) and another nematode species, Pristionchus pacificus (2.0 3 10 29 ; Weller et al 2014).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our empirical estimate of the spontaneous nuclear base substitution rate for C. elegans is similar to three previous estimates for the species using high-throughput sequencing of MA lines (Denver et al 2009(Denver et al , 2012Saxena et al 2019), but substantially lower than the first estimate, which was based on Sanger sequencing (9.1 3 10 29 ; Denver et al 2004). Additionally, our spontaneous base substitution rate is similar to estimates for the congeneric species C. briggsae (average 1.33 3 10 29 ; Denver et al 2012) and another nematode species, Pristionchus pacificus (2.0 3 10 29 ; Weller et al 2014).…”
Section: Discussionsupporting
confidence: 80%
“…However, the small indel rate for C. elegans from this study falls within the range reported from MA studies in a few metazoans (0.31 3 10 29 to 1.37 3 10 29 ; Katju and Bergthorsson 2019). Our genome-wide estimate of the small indel rate is considerably lower, namely , 6%, of the originally reported rate for C. elegans (Denver et al 2004), but similar to that recently reported by Saxena et al (2019). In another notable departure from previous results, which found that insertions outnumbered deletions in the C. elegans genome (Denver et al 2004), we find a strong deletion bias wherein deletions exceed insertions by threefold.…”
Section: Discussionsupporting
confidence: 75%
“…Finally, new data and expansion to new replicate populations allowed us to gain insights as to the rate, molecular spectrum and frequency dynamics of de novo mutation appearing during lab evolution. Our findings show some similarity to those found in mutation accumulation experiments, where selection is minimized ( Saxena et al 2019 ).…”
Section: Introductionsupporting
confidence: 86%
“…Besides its genetic tractability, use of this organism allows the analysis of evolution at different timescales. For example, experimental evolution can be used to study evolutionary processes in controlled environments on the order of 10–1000 generations (Gray and Cutter, 2014; Teotónio et al, 2017; Penley et al, 2018; Chelo et al, 2019; Saxena et al, 2019; Wernick et al, 2019). For longer timescales, a growing number of isolated and sequenced Caenorhabditis species can be used to study genetic differences responsible for species-level differences (Ting et al, 2018; Yin et al, 2018; Bi et al, 2019; Stevens et al, 2019).…”
Section: Introductionmentioning
confidence: 99%